Kebijakan Kriminalisasi Dalam Peraturan Daerah Dan Sinkronisasi Dengan Hukum Pidana Kodifikasi - Teguh Prasetyo (Fakultas Hukum Universitas Islam Indonesia, 2009)
The synchronization of criminal provisions in the residential decrees with the codified criminal law has not yet been made due to variety of the legal sources to which residential decrees may refer. Among the differences which need synchronization are the difference in the provisions of witnesses and also the differences in the interpretation made by the regulators.Keywords: Policy, criminalization, Local Government Regulation, synchronization.